Loss of epithelial Gq and G11 signaling inhibits TGFbeta production but promotes IL-33-mediated macrophage polarization and emphysema - John, A.E.; Wilson, M.R.; Habgood, A.; Porte, J.; Tatler, A.L.; Stavrou, A; Miele, G; Jolly, L; Knox, A.J.; Takata, M; Offermanns, S; Jenkins, R.G. (American Association for the Advancement of Science, 2016)
Heterotrimeric guanine nucleotide-binding protein (G protein) signaling links hundreds of G protein-coupled receptors with four G protein signaling pathways. Two of these, one mediated by Gq and G11 (Gq/11) and the other by G12 and G13 (G12/13), are implicated in the force-dependent activation of transforming growth factor-beta (TGFbeta) in lung epithelial cells. Reduced TGFbeta activation in alveolar cells leads to emphysema, whereas enhanced TGFbeta activation promotes acute lung injury and idiopathic pulmonary fibrosis. Therefore, precise control of alveolar TGFbeta activation is essential for alveolar homeostasis. We investigated the involvement of the Gq/11 and G12/13 pathways in epithelial cells in generating active TGFbeta and regulating alveolar inflammation. Mice deficient in both Galphaq and Galpha11 developed inflammation that was primarily caused by alternatively activated (M2-polarized) macrophages, enhanced matrix metalloproteinase 12 (MMP12) production, and age-related alveolar airspace enlargement consistent with emphysema. Mice with impaired Gq/11 signaling had reduced stretch-mediated generation of TGFbeta by epithelial cells and enhanced macrophage MMP12 synthesis but were protected from the effects of ventilator-induced lung injury. Furthermore, synthesis of the cytokine interleukin-33 (IL-33) was increased in these alveolar epithelial cells, resulting in the M2-type polarization of alveolar macrophages independently of the effect on TGFbeta. Our results suggest that alveolar Gq/11 signaling maintains alveolar homeostasis and likely independently increases TGFbeta activation in response to the mechanical stress of the epithelium and decreases epithelial IL-33 synthesis. Together, these findings suggest that disruption of Gq/11 signaling promotes inflammatory emphysema but protects against mechanically induced lung injury.